REDUCING LATENCY IN 5G-POWERED INDUSTRIAL IOT THROUGH EDGE INTELLIGENCE AND NETWORK SLICING (Journal of Multidisciplinary Sciences and Innovations, 2025)
The deployment of 5G in Industrial Internet of Things (IIoT) environments offers unprecedented opportunities for automation and real-time control. However, ultra-low latency remains a core requirement that centralized cloud architectures often fail to meet. This study investigates how latency in IIoT networks can be reduced by combining edge intelligence and network slicing. Using a simulated smart factory environment, the integration of local AI processing with dynamically allocated network slices shows a latency reduction of up to 45% compared to cloud-based systems. These results provide a scalable model for latency-sensitive IIoT applications in manufacturing, energy, and logistics.